Phylogenetic placement of the European sand gobies in Gobionellidae and characterization of gobionellid lineages (Gobiiformes: Gobioidei) - Thacker, Christine E. (Zootaxa, 2013)
The Mediterranean, northeastern Atlantic, and inland freshwaters of Europe and the Ponto-Caspian region host a distinct fauna of gobiiform fishes, including the sand gobies (Pomatoschistus Gill and related genera), all of which have been clas-sified in the most diverse goby group, the family Gobiidae. Recent molecular phylogenetic analyses have suggested that the sand gobies are not gobiids, and are instead part of their sister clade Gobionellidae (Thacker and Roje 2011). Phylo-genetic analysis of Pomatoschistus in the context of both gobiid and gobionellid taxa indicates that Pomatoschistus is part of Gobionellidae, specifically the Mugilogobius lineage. Gobionellidae includes 93 genera, which are arrayed into four lineages (Stenogobius, Mugilogobius, Periophthalmus and Northern Pacific). These lineages exhibit variation in charac-ters of the jaw and suspensorium, including the shapes and relative positions of the palatine, quadrate, and ectopterygoid. The observations of the palatopterygoid complex in Gobionellidae of Harrison (1989) and Larson (2001) are supported and augmented. Gobionellidae generally exhibit suspensoria that are overall more elongated and gracile than those of go-biids: the palatine/ectopterygoid pair features a very short (Periophthalmus lineage) or elongate, pointed palatine (Mugi-logobius, Northern Pacific, and Stenogobius lineages), with a relatively slender ectopterygoid and a short quadrate articulation. In Gobiidae, the palatine extends about halfway along the length of the ectopterygoid, and the ectopterygoid generally features a large, flat articulation with the quadrate. Suspensoria of Pomatoschistus and relatives are similar to those of other taxa in the Mugilogobius lineage. Placement of Pomatoschistus and relatives in Gobionellidae rather than Gobiidae is significant in that it indicates that sand gobies are not closely related to other European gobies, and has impli-cations for any comparative evolutionary or biogeographic studies.